Planetary diet and hidden risk: the significance of food allergies in vulnerable populations - Majsiak, Emilia; Traczyk, Iwona; Cabaj, Maria; Pukalyak, Solomiya; Samoliński, Bolesław K. (Alergologia Polska - Polish Journal of Allergology, 2026)
In response to growing health and environmental challenges, the planetary diet promoted by the EAT-Lancet Commission aims to integrate public health goals with environmental sustainability. It emphasises greater intake of plant-based foods: vegetables, fruits, legumes, and nuts while reducing meat and processed products. Although this diet helps prevent non-communicable diseases and lower greenhouse gas emissions, it may pose risks for individuals with food allergies. Legumes, nuts, and cereals contain allergenic proteins that can cause reactions ranging from mild symptoms to severe anaphylaxis. People with pollen allergies are also at risk due to cross-reactivity with similar plant proteins, known as pollen-food allergy syndrome. The rising popularity of “superfoods” that are unfamiliar in many diets may further increase allergic reactions among individuals unaware of structural similarities between known allergens and new plant proteins, posing new diagnostic and dietary challenges. To address these concerns, early diagnostic testing using component-resolved diagnostics is recommended for people with known pollen or food allergies before transitioning to a plant-based diet. This method provides a more accurate assessment of sensitisation and cross-reactivity risks. Individualised dietary planning, developed in close collaboration with a dietitian and allergist, is crucial when introducing novel plant proteins or replacing major animal-derived sources. For high-risk individuals, precautionary labelling, allergen avoidance education, and emergency action plans including the use of epinephrine autoinjectors are essential. Promoting gradual, clinically guided dietary shifts with ongoing medical supervision can help ensure that the planetary diet remains both sustainable and safe for sensitive populations.